Smart Contract’s Contributions to Mudaraba - Dhiaeddine Rejeb (Institute for Research and Community Empowerment (LPPM TAZKIA), 2021)
A Smart contract is a technology initiated in 1994 by Szabo and was taken over and became potentially highly applicable since the emergence of Blockchain technology. The idea that was developed by Szabo is to adopt digital self-executing contracts between parties without human intervention by using distributed ledgers to store contracts. This new technological era is intended to be used on a large scale in the financial sector. Insofar as the financial sector seeks to benefit as much as possible from these new technologies, Islamic finance also aims to position itself and integrate these innovations into its core. In the context of Islamic finance, the mudaraba contract (equity-based investment contract) despite its great economic benefits remains under-applied because of technical risks, investment obstructions, and Sharia restrictions. This work aims to study to what extent Smart contracts can contribute to the resolution of these drawbacks and the improvement of the mudaraba contract to be applied potentially by Islamic finance institutions. It is concluded that by the mudaraba contract can be enormously developed technologically, operationally, and from Sharia compliance perspective by applying smart contracts.